2020
DOI: 10.1111/vco.12579
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of copper chaperones sensitizes human and canine osteosarcoma cells to carboplatin chemotherapy

Abstract: Osteosarcoma (OSA) is the most common primary bone cancer in children, adolescents and dogs. Current combination surgical and chemotherapeutic treatments have increased survival. However, in recurrent or metastatic disease settings, the prognosis significantly decreases, representing an urgent need for better second-line and novel chemotherapeutics. The current gold standard for combination chemotherapy in OSA often includes a platinum agent, for example, cisplatin or carboplatin. These platinum agents are shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…57,58 DC_AC 50, a small molecule inhibitor of Atox1, has been found to limit copper intake and sensitize cancer cells to platinum drugs. 59,60 In this study, we found that FGF13 simultaneously regulates the expression and distribution of hCTR1 and ATP7A to reduce drug influx and promote drug sequestration and efflux when cancer cells are exposed to platinum drugs. The FGF13-induced regulation of hCTR1 and ATP7A depends on the microtubule-stabilizing effect of FGF13.…”
Section: The Possibility Of Targeting Fgf13 For Cancer Treatmentmentioning
confidence: 72%
See 1 more Smart Citation
“…57,58 DC_AC 50, a small molecule inhibitor of Atox1, has been found to limit copper intake and sensitize cancer cells to platinum drugs. 59,60 In this study, we found that FGF13 simultaneously regulates the expression and distribution of hCTR1 and ATP7A to reduce drug influx and promote drug sequestration and efflux when cancer cells are exposed to platinum drugs. The FGF13-induced regulation of hCTR1 and ATP7A depends on the microtubule-stabilizing effect of FGF13.…”
Section: The Possibility Of Targeting Fgf13 For Cancer Treatmentmentioning
confidence: 72%
“… 57 , 58 DC_AC 50, a small molecule inhibitor of Atox1, has been found to limit copper intake and sensitize cancer cells to platinum drugs. 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…To provide deeper insight into the role played by the prognostic risk score model in HNSC, we performed some further analyses. Several lines of evidence suggest that copper and its transporter could affect the outcome of chemotherapy [ 51 , 52 , 53 ]. So, we predicted the sensitivity towards chemotherapeutics in both high- and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Atox1 may participate in the regulation of genes encoding superoxide dismutase 3 [37], pluripotency factor OCT4 [38], and NADPH oxidase organizer p47phox [39]. Deletion of Atox1 results in increased resistance to cDDP [40,41], perhaps due, at least in part, to impairment of nuclear targeting of Pt drugs to elicit DNA damages of the lethal effects [42]. and then to ATP7A/ATP7B at the Trans-Golgi Network (TGN) in the cytosol via the help of glutathione (GSH).…”
Section: Cu Chaperones In Intracellular Cddp Traffickingmentioning
confidence: 99%